2021
DOI: 10.1002/adhm.202100862
|View full text |Cite
|
Sign up to set email alerts
|

In–Situ‐Sprayed Dual‐Functional Immunotherapeutic Gel for Colorectal Cancer Postsurgical Treatment

Abstract: Surgery remains the most preferred treatment options for colorectal cancer (CRC). Paradoxically, local recurrence and distant metastasis are usually accelerated postsurgery as a consequence of local and systemic immunosuppression caused by surgery. Therefore, modulating tumor postoperative immune microenvironment and activating systemic antitumor immunity are necessary supplementaries for CRC therapy. Here, an in-situ-sprayed immunotherapeutic gel loaded with anti-OX40 antibody (iSGels@aOX40) is reported for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Generally, typical immunosuppressive status includes patients with hematological diseases, tumor, oral immunosuppressive medications, solid-organ transplant, stem cell transplant, or bone marrow transplant, and atypical immunosuppressive status includes patients with diabetes mellitus, liver cirrhosis, and burns ( Mylotte and Tayara, 2000 ; Li et al., 2021 ; Willis et al., 2021 ). Studies revealed that immunosuppression could result from critical surgery as well ( Si et al., 2021 ), and sometimes postoperative patients are susceptible to infections caused by opportunistic pathogens ( Mada et al., 2020 ; Shipman et al., 2021 ). IS patients with infections may present with atypical signs and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, typical immunosuppressive status includes patients with hematological diseases, tumor, oral immunosuppressive medications, solid-organ transplant, stem cell transplant, or bone marrow transplant, and atypical immunosuppressive status includes patients with diabetes mellitus, liver cirrhosis, and burns ( Mylotte and Tayara, 2000 ; Li et al., 2021 ; Willis et al., 2021 ). Studies revealed that immunosuppression could result from critical surgery as well ( Si et al., 2021 ), and sometimes postoperative patients are susceptible to infections caused by opportunistic pathogens ( Mada et al., 2020 ; Shipman et al., 2021 ). IS patients with infections may present with atypical signs and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In female black mice, B16F10 melanoma tumors are established in armpits and then surgically debulked by ≈2/3 to simulate nonideal surgical conditions. [ 22 ] The mice are randomly divided into four groups, including i) the control group (without treatment), ii) the TPU nanotextile dressing containing free DOX group, iii) the wearable electro‐thermal therapy (ETT) group, and iv) the wearable combined therapy group. The stretchable electronic patch is conformally attached to the surgical wound site with abundant exudate for wearable treatments, as shown in Figure S21 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In the implant group, the residual tumors were eradicated after surgery, which helped inhibit distal tumor metastasis and induced immune-memory effects resisting the re-challenge experiment. Recently, Si et al [ 21 ] further improved a nanogel implant to an in-situ -sprayed gel delivering anti-OX40 antibody, which demonstrated the promising therapeutic potential of CRC. This improved nanogel modulated the suppressive immune microenvironment by inhibiting the activity of cyclo-oxygenase-2 (COX-2); as a result, the loaded aOX40 was gradually released for over 20 days, serving as an immune agonistic antibody.…”
Section: Application Of Nanotechnology In Conquering Therapeutic Resi...mentioning
confidence: 99%